RETRACTED ARTICLE: The Role of Justice Law Enforcement by Judges in Handling Criminal Cases - Nani Widya Sari; Oksidelfa Yanto; Guntarto Widodo; I Nyoman Putu Budiartha (Fakultas Hukum, Universitas Warmadewa, 2025)
This article has been retracted with agreement of the journal editors. The retraction is due to a significant overlap with an article by the same authors that has been published in another journal (Legalis : Journal of Law Review). This constitutes a case of duplicate publication, which is a breach of our journal's publication ethics policy. The authors apologize to the readers and editors of both journals for this oversight. The journal is committed to upholding the integrity of the scientific record.